Mapping coral reefs growth using drone imagery in Gili Labak Island, Sumenep District, East Java, Indonesia - FIRMAN FARID MUHSONI; ADNIN TAMHIDA SHOBRINA SALSABIL; SAFA SAFA; MUHAMMAD ZAINURI; ABU BAKAR SAMBA; ELYS FAUZYAH; DEDI IRAWAN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Muhsoni FF, Salsabil ATS, Safa, Zainuri M, Samba AB, Fauzyah E, Irawan D. 2025. Mapping coral reefs growth using drone imagery in Gili Labak Island, Sumenep District, East Java, Indonesia. Biodiversitas 26: 1180-1188. The benthic habitat serves as the dwelling place for diverse aquatic organisms, primarily characterized by coral reefs. Meanwhile, Gili Labak Island, Sumenep District, East Java, Indonesia has a well-preserved marine ecosystem, including coral reefs, seagrass beds, and other marine organisms. A drone is one of the platforms that can be used to map benthic habitats, which has the advantages of relatively low cost, the ability to monitor temporal changes over a short period, and the capacity to use multispectral sensors. In this research, drone imagery or Unmanned Aerial vehicles from 2021 and 2022 were used. The classification method used was the supervised maximum likelihood, and accuracy testing was conducted using a confusion matrix. In addition, coral reef cover data was directly collected using the Underwater Photo Transect (UPT) method in September 2023. The classification results using the supervised maximum likelihood method with drone imagery were able to identify changes in coral reefs from 2021 to 2022. The accuracy test results showed an overall accuracy ranging from 74.20% to 86.47% (2021 data) and 79.94% to 90.87% (2022 data). The kappa coefficient values obtained were 71.80% to 82.72% (2021 data) and 70.33% to 89.25% for 2022 data. Drone imagery has proven to be useful in observing coral growth through changes in coverage. In this study, changes in live coral coverage (Acropora, Goniastrea, Mycedium, Pocillopora, Porites, and Stylophora) between 2021 and 2022 were observed. At Station 1, the coral coverage increased from 176.77 m² (30.95%) to 323.18 m² (57.43%). At Station 2, it decreased from 740.25 m² (75.21%) to 462.61 m² (47.68%). At Station 3, it decreased from 422.11 m² (94.91%) to 377.44 m² (86.26%). The percentage of coral reef cover using the average Underwater Photo Transect (UPT) method was 61.66%. This study demonstrates that the application of high-resolution drone imagery, along with mapping and monitoring methods, can be used to detect changes in coral reef conditions, providing valuable information for management and conservation strategies.